Changes in the microbial communities in vacuum-packaged smoked bacon during storage. (February 2019) - Li, Xinfu; Li, Cong; Ye, Hua; Wang, Zhouping; Wu, Xiang; Han, Yanqing; Xu, Baocai
Abstract: This study aimed to gain deeper insights into the microbiota composition and population dynamics, monitor the dominant bacterial populations and identify the specific spoilage microorganisms (SSOs) of vacuum-packed bacon during refrigerated storage using both culture-independent and dependent methods. High-throughout sequencing (HTS) showed that the microbial composition changed greatly with the prolongation of storage time. The diversity of microbiota was abundant at the initial stage then experienced a continuous decrease. Lactic acid bacteria (LAB) mainly Leuconostoc and Lactobacillus dominated the microbial population after seven days of storage. A total of 26 isolates were identified from different growth media using traditional cultivation isolation and identification method. Leuconostoc mesenteroides and Leuconostoc carnosum were the most prevalent species since day 15, while Lactobacillus sakei and Lactobacillus curvatus were only found on day 45, suggesting that they could be responsible for the spoilage of bacon. Serratia, Rahnella, Fusobacterium and Lactococcus underwent a dramatic increase at some point in individual batchs which may be considered as potential contributors to the spoilage. Highlights: Both culture-dependent and culture-independent methods were applied. Greater diversity were observed at the initial stage and then continuous decrease. Leuconostocs and Lactobacillus takes absolute dominate after initial storage. Leuconostocs mesenteroides, Leuconostocs carnosum, Lactobacillus sakei, Lactobacillus curvatus may be the SSOs. The load of microorganisms are positively related to the storage time.